Tissue-specific regulation of translational readthrough tunes functions of the traffic jam transcription factor. - Karki, P.; Carney, T.D.; Maracci, C.; Yatsenko, A.S.; Shcherbata, H.R.; Rodnina, M.V. (Nucleic Acids Research, 2022)
Translational readthrough (TR) occurs when the ribosome decodes a stop codon as a sense codon, resulting in two protein isoforms synthesized from the same mRNA. TR has been identified in several eukaryotic organisms; however, its biological significance and mechanism remain unclear. Here, we quantify TR of several candidate genes in Drosophila melanogaster and characterize the regulation of TR in the large Maf transcription factor Traffic jam (Tj). Using CRISPR/Cas9-generated mutant flies, we show that the TR-generated Tj isoform is expressed in a subset of neural cells of the central nervous system and is excluded from the somatic cells of gonads. Control of TR in Tj is critical for preservation of neuronal integrity and maintenance of reproductive health. The tissue-specific distribution of a release factor splice variant, eRF1H, plays a critical role in modulating differential TR of leaky stop codon contexts. Fine-tuning of gene regulatory functions of transcription factors by TR provides a potential mechanism for cell-specific regulation of gene expression.